2015
DOI: 10.14737/journal.aavs/2015/3.12.689.693
|View full text |Cite
|
Sign up to set email alerts
|

Reverence of Community towards Grassroot Livestock Innovation: Responding to Stakeholders Need against Sub-Clinical Mastitis in Amreli District, Gujarat, India

Abstract: M astitis is a disease of economic importance causing havoc in dairy sector throughout the world. National mastitis control program envisages minimizing spread of infection, protecting mammary gland tissue and curtailing entry of pathogens through teat orifice. Farm productivity has been limited with lack of appropriate technologies to meet location specific requirements (Kadivendi et al., 2015). Periodic assessment of milk is important to know the health status of udder (Syed et al., 2009). Dairy farmers diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Gupta (2013) opined that ethical value by academic institutions towards local knowledge holders were not enforced adequately. Evidence was shared wherein engagement with civil society had brought out different challenges and indigenous healer had reported new role of medication which was earlier confirmed for scientific efficacy against mastitis, a common problem affecting welfare of livestock (Devgania et al, 2015). Learning from such findings illustrates nature of available knowledge with civil society and generation of research questions to scientific community.…”
Section: Reinforcement Of Innovations In Traditional Knowledgementioning
confidence: 97%
“…Gupta (2013) opined that ethical value by academic institutions towards local knowledge holders were not enforced adequately. Evidence was shared wherein engagement with civil society had brought out different challenges and indigenous healer had reported new role of medication which was earlier confirmed for scientific efficacy against mastitis, a common problem affecting welfare of livestock (Devgania et al, 2015). Learning from such findings illustrates nature of available knowledge with civil society and generation of research questions to scientific community.…”
Section: Reinforcement Of Innovations In Traditional Knowledgementioning
confidence: 97%
“…Gupta et al (1997) argues that collaborative learning can be enjoyable and meaningful if only dialogues between farmers-scientists are matched with ethical parlance. Sharing of scientific results with healer and enabling interactive meeting with villagers resulted in sharing of empathetic livestock innovation (Devgania et al, 2015). These novel livestock medications had emerged with participation of outstanding knowledge holders and livestock owners by addressing livestock ailments (Ravikumar et al, 2016b).…”
Section: Framework For Livestock Innovationsmentioning
confidence: 99%
“…This is in concurrence with Gupta (1997) who shared that participatory learning through peer group interaction offer alternatives or variations known to healers. Models of engaging community or stakeholders in disclosing such variations in novel medications were shared through interaction between healer and livestock farmers (Devgania et al, 2015). Technical, ethical and methodological challenges in IKRS have to be unearthed (McCorkle, 1995).…”
Section: Advances In Animal Andmentioning
confidence: 99%
“…An experimental research study at farmer's field for testing indigenous medication against mastitis revealed a refreshing approach. New knowledge was gained upon sharing scientific test results with community and knowledge holder (Devgania et al, 2015). Formal institutions need to gear up to evaluate IKRS scientifically at farmer's situation.…”
Section: Who Can Sustain Ikrs and Creative Spirit Of Informal Societymentioning
confidence: 99%